(untitled) (Tikrit Journal of Veterinary Science, 2025)
In diabetic rats given an experimental treatment, the impact of alcoholic pumpkin seed extract (Cucurbita pepo L.) on hepatocellular mortality and inflammation was studied. One intraperitoneal injection of streptozotocin (STZ; 40 mg/kg) caused diabetes in male rats, followed by a dose of pumpkin seed extract (200 mg/kg), for three months, given every other day. TNF-α levels in diabetic rats treated with pumpkin seed extract improved to normal. Pumpkin seed extract also prevented arise in p53, Bax, caspases-3, 8, and 9, lessened hepatic damage of DNA, and slowed the rise in TNF-α levels. It also regulated apoptosis by increasing the production of Bcl-2 protein. Based on current research, pumpkin seeds may shield the liver from necrosis, apoptosis, inflammation, and DNA damage by enhancing the redox state, inhibiting p53 and caspases, and raising Bcl-2 protein. As a result of enhancing apoptotic signals, pumpkin seeds have a great deal of therapeutic promise for managing diabetes and its adverse effects on the liver.